Pengaruh Sudut Vertikal Terhadap Hasil Ukuran Jarak dan Beda Tinggi Metode Trigonometris Menggunakan Total Station Nikon DTM 352 - Parseno Parseno; Yulaikhah Yulaikhah (Faculty of Engineering, Universitas Gadjah Mada, 2010)
The measurement of heigh differences using trigonometric technique, and Total Station NikonDTM 352 is used.It is identified that the use of different vertical angle will produce differentheights for the same point. It is interesting to analyse further that, the errors of distance andheight differences in trigonometric technique are as the function of vertical angle. This researchtries to investigate the phenomenom mentioned above: is there sistimatical error? and how tocorect them ?This research is initially arranged to include some steps: (1) preparation of instruments, (2)measurement of distance and height differences in study area using spirit levelling andtrigonometric levelling, (3) Data processing including correction of differences in heightmodelling. Evaluation was carried out by comparing both data of observed height differences.Based on the result of the statistical test, it is found that the variety of vertical angles do notaffect the computed distance and height differences using Total Station. From the data exercisesresulted that the accuracy of height differences is affected by distance and vertical angle,however for the distance up to 800 m, the improvement is not signifcant. In addition the fieldobservations also show that the distance greater than 50m , the contribution of the accuracy ofangle to the change of the accuracy of height differences is greater than the contribution of theaccuracy of the distances.Keywords: height differences,trigonometric levelling, trigonometric technique, Total Station.